Biblical Hospitality and the Formation of Contextual Church Communities in Indonesia - Yoas Tanugraha; Benny Sinaga (Indonesian Journal of Christian Education and Theology, 2026)
This study aims to construct a theological understanding of hospitality within the unity of the Old and New Testaments and to formulate a contextual model of church practice for Indonesia. The background of this study is the decline of hospitality in the modern church, which tends to shift from deep relationships to formal and functional practices. The method used is descriptive-analytical qualitative research employing biblical theology, contextual hermeneutics, and socio-historical approaches. The texts analyzed include Genesis 18 and Leviticus 19:33–34 (Old Testament), as well as Acts 16:13–40, Romans 12:13, and Hebrews 13:2 (New Testament). The research findings indicate that in the Old Testament, hospitality is a response of faith to God and an expression of covenantal relationship, whereas in the New Testament, hospitality evolves into a means of participation in God’s mission through personal and community-based relationships centered on the home.